2015
DOI: 10.1002/1873-3468.12048
|View full text |Cite
|
Sign up to set email alerts
|

The PtdIns3‐phosphatase MTMR3 interacts with mTORC1 and suppresses its activity

Abstract: Macroautophagy is a major intracellular degradation system. We previously reported that overexpression of phosphatase‐deficient MTMR3, a member of the myotubularin phosphatidylinositol (PI) 3‐phosphatase family, leads to induction of autophagy. In this study, we found that MTMR3 interacted with mTORC1, an evolutionarily conserved serine/threonine kinase complex, which regulates cell growth and autophagy in response to environmental stimuli. Furthermore, overexpression of MTMR3 inhibited mTORC1 activity. The N‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 48 publications
(79 reference statements)
1
23
0
Order By: Relevance
“…MTMR7 decreased phosphorylation of ERK1/2 by MEK1/2 on 202/185TEY204/187 and of AKT on S473/T308 residues. Hence, MTMR7 did not block single mTORC1/2 complexes, as described for MTM1 [19, 20] or MTMR3 [21], what would have abrogated phosphorylation exclusively on either SER473, which is part of the AKT-mTORC2 feed forward loop, or THR308, which is targeted by PI3K-PDK1. Instead, MTMR7 inhibited upstream components in these pathways resulting in a decreased production of the lipid second messenger PI(3)P. MTMR8 binds PI3K thereby reducing PI3K activity [22].…”
Section: Discussionmentioning
confidence: 96%
“…MTMR7 decreased phosphorylation of ERK1/2 by MEK1/2 on 202/185TEY204/187 and of AKT on S473/T308 residues. Hence, MTMR7 did not block single mTORC1/2 complexes, as described for MTM1 [19, 20] or MTMR3 [21], what would have abrogated phosphorylation exclusively on either SER473, which is part of the AKT-mTORC2 feed forward loop, or THR308, which is targeted by PI3K-PDK1. Instead, MTMR7 inhibited upstream components in these pathways resulting in a decreased production of the lipid second messenger PI(3)P. MTMR8 binds PI3K thereby reducing PI3K activity [22].…”
Section: Discussionmentioning
confidence: 96%
“…Another study (Taguchi‐Atarashi et al., ) uncovered a negative regulatory role of MTMR3 in autophagosome formation. Further studies (Hao et al., ) showed that MTMR3 associated with mTOR and suppressed its activity in manners independent of MTMR3 enzymatic activity, suggesting the bimodal actions of MTMR3 in the autophagy regulation. Notably, MTMR3 was found to interact with MTMR4 in cells.…”
Section: Discussionmentioning
confidence: 98%
“…However, the subcellular localization of MTMR4 is not fully understood. Moreover, several MTMRs have been implicated in autophagy (Al‐Qusairi et al., ; Hao et al., ; Liu, Lv, Liu, Qu, & Shen, ; Noda, Matsunaga, Taguchi‐Atarashi, & Yoshimori, ; Taguchi‐Atarashi et al., ; Vergne & Deretic, ; Vergne et al., ; Zou et al., ) and lysosomal storage disorder‐related human diseases. MTM1 has been shown to be mutated in congenital X‐linked centronuclear or myotubular myopathy (XLCNM) (Kioschis et al., ), while MTMR2 and MTMR13 have been shown to be mutated in Charcot‐Marie‐Tooth (CMT) neuropathy (Azzedine et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Myotubularin‐related protein 3 (MTMR3) is a PtdIns3P phosphatase found to be important for autophagy . MTMR3 depletion or overexpression of a phosphatase‐deficient mutant, lead to increased autophagosome formation, whereas overexpression of wild‐type MTMR3 resulted in smaller autophagosomes and a net reduction in autophagic activity (Fig.…”
Section: Ptdins‐binding Domains and The Autophagy Proteins That Contamentioning
confidence: 99%
“…Upon nutrient depletion, mTORC1 activity decreases, leading to ULK1 dephosphorylation, activation, and autophosphorylation , as well as its phosphorylation of ATG13, FIP200, Beclin1, and VPS34 . Both wild‐type and phosphatase‐deficient MTMR3 inhibit mTORC1 activity, indicating that this protein may regulate autophagy both at the level of PtdIns3P and mTORC1 . There are 16 different MTMR proteins, nine of which possess catalytic activity, dephosphorylating PtdIns3P and PtdIns(3,5)P 2 at the D‐3 position.…”
Section: Ptdins‐binding Domains and The Autophagy Proteins That Contamentioning
confidence: 99%